Formulasi Pasta Gigi Gel Ekstrak Etanol Bawang Dayak (Eleutherine bulbosa (Mill.) Urb.) - Husnul Warnida; Ade Juliannor; Yullia Sukawaty (Jurnal Sains Farmasi & Klinis, 2016)
Dental caries is a disease of tooth decay that starts from the surface and evolve in the direction of the tooth, beginning with the process of tooth demineralization. Tooth decay is usually caused by the bacterium Streptococcus mutans. Bawang Dayak (Eleutherine bulbosa (Mill.) Urb.) has antibacterial activity due to its compound i.e. flavonoid, fenol, triterpenoid, dan antrakuinon. This study aims to formulate the bawang dayak ethanol extract into a stable gel toothpaste. Bawang dayak ethanol extract 2,5% was formulated in 5 formulas with varying degree of sorbitol (5 - 50%) and carboxymethyl cellulose (3 - 7%). Physical stability of bawang dayak ethanol extract gel toothpastes were evaluated including organoleptic and homogeneity test, pH measurement, viscosity measurement, spreading test, and freeze-thaw cycling test. The result showed bawang dayak ethanol extract gel toothpastes have pH range of 5.50 - 5.80, spreading area 4.61 - 5.82, viscosity value 17066 - 99877 mPas. Organoleptic and homogeneity in 7 days showed two layers color of gel toothpaste. Consistency test and Freeze-thaw cycling test results showed no change in organoleptic, homogeneity, pH, and viscosity of gel toothpastes.